Subir Bahia: uma rua na encruzilhada da memória patrimonial e de novas escritas urbanas - Joao Marcos Veiga de Oliveira (2015)
This dissertation aims at investigating the space at Rua da Bahia, in the city of Belo Horizonte. as time frame, significant moments of delimitation and uniqueness of such street, and disputes over its representation were chosen. By the critical analysis of reports and diagnoses of the public authorities, as well as from literature and the press, this research hasanalyzed the formation of social and affective centralization of such street timed between the inauguration of the capital of Minas and the 1930s. Always under the scope of the local and global context of the issues linked to patrimony, and identifying controversies and resumptions, the study highlighted, in a second moment, how since the 1990s specific ideas of tradition and identity have been evoked on projects for such place, such as the cultural axis live Rua da Bahia and Rua da Bahia 24 hours, legitimating proposals of urbanistic intervention and the stimulation of that memory projected into the public space, throughmonuments and statues. In a third moment, through field research, it intended to show how, beyond the conceived look of urbanistic projects, urbanity is hybridized by different identities, centralities and temporalities, which result in appropriations and counter-uses of the social sites that conform the contemporary Rua da Bahia.